Clinical outcomes and severe complications of hospitalised children and adolescents with varicella in central Switzerland: a retrospective observational study (Swiss Medical Weekly, 2025)
AIM: Recent data on clinical complications and mortality among hospitalised children and adolescents due to varicella are unavailable in Switzerland. The aim of the study was to explore data on severe varicella complications in hospitalised children before the introduction of a universal varicella vaccination recommendation, which the Swiss Federal Office of Public Health implemented in January 2023.METHODS: This was a retrospective observational study of children hospitalised with varicella between 01.01.2010 and 31.03.2020 at a tertiary children’s hospital in central Switzerland serving approximately 10% of the Swiss population. The inclusion criteria were acute varicella and/or related complications.RESULTS: A total of 95 patients were identified. The median age at onset was 4 years (range: 2 months to 13 years) and the peak age of patients was between 1 and 4 years. 53 had mild and 42 patients had severe varicella-associated complications (8 had >1 severe complication). The most common severe complications were bacterial skin and soft tissue infections (n = 28), invasive secondary bacterial infections (n = 18), and central nervous system-related complications (n = 12). Admission to the paediatric intensive care unit and surgical intervention were required in 11 (12%) and 16 (17%) patients, respectively. Two previously healthy school-age children died because of secondary bacterial infections.CONCLUSION: Our results demonstrate that varicella can cause severe and even fatal complications in children living in a highly developed country. This study provides valuable clinical data on severe varicella complications in hospitalised children from a large catchment area of Switzerland, facilitating future data comparison of the disease burden before and after the introduction of universal varicella vaccination in Switzerland.